KEPEMILIKAN KENDARAAN DAN POLA PERJALANAN DI WILAYAH JABODETABEK - Bambang Susantono; Wimpy Santosa; Arif Budiyono (Jurnal Transportasi, 2011)
Jakarta and Jabodetabek area (Greater Jakarta) developed very rapidly in the last ten years. In addition, the development in this region led to the increased of motor vehicle ownership, particularly motorcycles. The growth in the number of vehicles that are not followed by the addition of a sufficient length of road causing traffic problems in the Jabodetabek area. Within about 10 years, travel time increased or travel speed dropped significantly in Jakarta. In addition, the implementation of several development programs, as results of the Study on Integrated Transportation Master Plan for the Jabodetabek (SITRAMP Jabodetabek) are not going according to plan, caused by weak legislation, lack of financial resources, difficulties in land acquisition, institutional constraints, and constraints in the implementation of traffic restrictions.Keywords: motor vehicle ownership, travel time, SITRAMP Jabodetabek